Scaling left ventricular mass in adolescent female soccer players - Diogo V. Martinho; João Valente-; Manuel J. Coelho-; Arturo O. Gutiérrez; João P. Duarte; Pedro Lourenço-Farinha; Leonardo G. O. Luz; João Gonçalves-Santos; Dalmo R. L. Machado; Neiva Leite; Jorge Conde; Joaquim M. Castanheira; et al. (BMC, 2020)
Abstract Background The aim of the study was to examine the contribution of chronological age (CA), skeletal maturation, training experience and concurrent body size descriptors, to inter-individual variance in left ventricular mass (LVM) among female adolescent soccer players. Methods The sample included 228 female soccer players 11.8-17.1 years. Training experience defined as years of participation in competitive soccer (range 2-9 years), was obtained by interview. Stature, body mass and skinfolds (triceps, medial calf) were measured. Fat mass was estimated; Fat-free mass was derived. LVM was assessed by echocardiography. Skeletal maturity status was as the difference of skeletal age (SA, Fels method) minus CA. Results Fat-free mass was the most prominent single predictor of LVM (R2 = 36.6%). It was associated with an allometric coefficient close to linearity (k = 0.924, 95%CI: 0.737 to 1.112). A significant multiplicative allometric model including body mass, fat-free mass, CA, training experience and skeletal maturity status was also obtained (R = 0.684; R2 = 46.2%). Conclusion Stature has limitations as a valid size descriptor of LVM. Body mass, fat-free mass, training experience, CA, body mass and skeletal maturity status were relevant factors contributing to inter-individual variability in LVM.